AUSTRALIA THROUGH THE EYES OF SOCIAL MEDIA: NATIONAL IDENTITY AND REPRESENTATION - Abdukarimova Kamola (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In the digital age, social media platforms have become vital tools for informal learning and cultural exposure. This thesis investigates how Australia is portrayed on platforms such as YouTube and TikTok, focusing on their influence on youth perceptions of national identity. Through qualitative analysis of visual content and online interaction, the research explores how digital representations affect the global image of Australia. The study reveals that while social media enhances cultural engagement and curiosity, it also reinforces certain stereotypes. These findings highlight the need for media literacy in interpreting such portrayals.